Seroprevalence of Toxoplasma gondii in Gallus domesticus in Havana, Cuba - Grandía G., Raiden (2016)
The aim of this study was to determine the seroprevalence of T. gondii in Gallus domesticus in Havana, Cuba. Three hundred serum samples were collected from White Leghorn pullets L33 in growing stage in 2015. Samples represented 100 birds per batch incorporated into the poultry unit from different origins. Samples were evaluated by an ELISA inhibition test and data was analyzed by the Chi-square and Duncan tests to compare proportions of positive birds among batches. A relatively low seroprevalence of T. gondii was found (9.6%), similar to other findings reported internationally. Significant differences (p=0.0001) in the prevalence of T. gondii among the three bird batches were found. It is concluded that the seroprevalence of T. gondii in Gallus domesticus in Havana is low, though this constitutes a risk of infection for susceptible human and animal populations.